Effects of economic freedom on bank efficiency, output reallocation and profit convergence in the Asean-5 banking sector - Yap, Woon Kan (2020)
This thesis consists of three stand-alone, yet inter-related studies that delve into the underlying dynamics concerning economic freedom, bank efficiency, output reallocation and profitability convergence. Notably, these studies look into the impacts that different sources of economic freedom have on the banking sector from various perspectives. The empirical analyses of these studies are carried out by employing an identical sample, which comprises 135 banks operating in the ASEAN-5 countries from 2010 to 2015. The first study examines the impacts of economic freedom on bank cost efficiency, thereafter, the manners in which these freedom-induced impacts are conditioned by the prevailing rule of law, are duly ascertained. To this end, the rule of law is found to have important threshold effects on the impact of economic freedom on bank cost efficiency. A smaller sized-government is uncovered to reduce bank cost efficiency unless a certain level of the rule of law is observed. This indicates that a contraction of fiscal spending to reduce the government size, is generally found to impair bank cost efficiency. However, the reduction in cost efficiency is mitigated when there is sufficient protection of creditors’ rights and debt recovery process, measured by the rule of law. Similarly, the positive effects that a liberalised credit market has on bank cost efficiency is not apparent until a certain level of the rule of law is observed. This suggests that deregulation without sufficient regulatory forces is expected to bring about issues on moral hazard and excessive risk-taking, which subsequently lead to lower bank cost efficiency unless the rule of law is observed to a certain degree. As a result, reforms to promote a greater level of economic freedom should be preceded by policies that foster the rule of law. The second study extends the first study’s objective by ascertaining how economic freedom, through the moderation of cost inefficiency, eventually affects allocative efficiency of the ASEAN-5 banking sectors as exemplified by the reallocation of banking outputs or the factors of production. Firstly, the findings of this study affirm the prevalence of an efficient output reallocation mechanism that is underlying the ASEAN- 5 banking sectors. Such a conclusion is made when the reallocative effects instigated by competitive pressure, are found to be proportional to bank cost inefficiency. Therefore, upon coalescing the findings of the first and second study, conclusions can be drawn about the effects of economic freedom on the reallocation of banking outputs. Once the rule of law has been observed to a certain degree, a higher level of freedom in the credit markets does not only improve bank cost efficiency as revealed in the first study but it also eases the competitive pressure that saddles the incumbent banks. This suggests that relaxing the restrictions on banking activities is expected to enlarge the bankable segment. As a result, the need for banks to compete among themselves abates. On the other hand, despite the reduced bank cost efficiency following a reduction in government size as uncovered in the first study, the underlying efficient output reallocation mechanism will ensure that the least cost efficient banks are the first ones to be displaced. Hence, this eventually increases the overall stability of the banking sectors in the long-run. Lastly, the third study of this thesis examines how economic freedom facilitates the betaconvergence of bank profitability to the industry’s long-run equilibrium, which is the level that all incumbent banks tend to, upon behaving competitively. This arguably constitutes an alternate approach to the second study that evaluates the contribution of economic freedom towards fostering allocative efficiency in the banking sector. While the second study deems the banking sector allocatively efficient when banking outputs are optimally reallocated, the third study embodies the neo-classical prediction that allocative efficiency only transpires when banks’ performances equalise. The results yielded from this study show that the ASEAN-5 banking sectors are generally competitive as both bank profits and the ROAA are found to beta-converge to a competitive level. Although there is no evidence that the pace of convergence is significantly determined by the prevailing level of economic freedom, there are certain thresholds for both the extent of freedom in the credit markets and the size of government, to satisfy, in order for bank profitability to beta-converge significantly. Incidentally, the findings yielded from all of the empirical studies encapsulated in this thesis stand up to the tests for robustness, which include: 1) varying the estimation strategies used; 2) censoring the sample and 3) altering the proxies used for the variables of interest. Therefore, the conclusions generated from the findings of this thesis are robust.